Not all things burnt are caramel! / Nadia Liana Mohd Karim and Noor Saliza Salmi - Mohd Karim, Nadia Liana; Salmi, Noor Saliza (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
I'm an avid cooking show follower to the extent that I find solace watching cooking shows on television. Partly, this is due to my daytime job as an educator in the area of food and service management that drive my curiosity and passion about the gastronomic world. So when I watch cooking shows, I don't just collect recipes but I learn, relearn, and sometimes I doubt. Based on my observations, some chefs on television has been abusing jargons so much so that viewers might start to believe the wrong things right. Get what I mean? My current concern is the usage of the word caramelization'. The moment we read 'caramel', most of people can relate it to the deep, complex sweetness, rooted from basic sugar with a bit more character than plain ones. Definitively, caramel is the outcome of cooking white sugar on its own until it turns amber.